Library counter talk: communication encounters between counter staff and international students - Rafik-Galea, Shameem; Ishak, Wan Irham; Baharuddin Marji, Aliyah (Elsevier, 2012)
Library patron communication is considered an important form of customer service. The professional use of language by library front desk staff should reflect the professional image of not only the library but also of the university itself. Library front desk staffs are responsible for various types of transactions. This paper presents and discusses the findings based on a qualitative study which investigated language use and communication strategies employed by the library front desk staff and international students of a university. The findings indicate that there is an over reliance of the use of several forms of communication strategies such as holophrastic strategy apart from the use of lexical repetition and literal translation.